Feedback bit allocation in distributed antenna array systems - Shuai ZHANG; Peng PAN; Cui WANG (Dianxin kexue)
In a frequency division duplex communication system,precoding at the base station usually requires terminal feedback channel state information.In a distributed array system,the channel conditions between the terminal and different access nodes in the cell are different because multiple access nodes are arranged at different locations in the cell.When the resources for feedback channel state information are limited,the allocation method of feedback bit needs to be optimized to improve the overall performance of the system.In a multi-user distributed array system,an access node selection method based on distance threshold was adopted.Based on this method,the quantization characteristics of the random vector quantization codebook and the Taylor expansion method were used to derive the system quantization capacity loss,and then an approximate expression was given.Based on this expression,a feedback bit allocation method was proposed.Compared with other allocation methods,the method of this paper was more universal because it did not limit the number of access nodes selected by the user.The simulation results show that the strategy proposed is superior to the traditional equal-bit allocation scheme and can obtain better performance when the feedback resources are limited.